Reducing Deviations in Weekly Scheduling At the Finishing Stage of Multi-Family Buildings by Implementing a Model Guide for Digital Agreement Management - Dominguez, Jheremy (2025)
The article addresses the problem of deviations in the weekly schedule during the finishing stage of multifamily projects. The lack of effective methodologies to manage agreements between stakeholders generates delays, cost overruns and coordination problems. A model guide for the digital management of agreements was developed and implemented, using the ClickUp tool to record, assign and track commitments in real time. After its application, an increase in compliance with planned activities (77.27%), a reduction in rescheduling (18.18%) and an increase in the productivity of key stakeholders was observed. The results demonstrate that the digitization and structuring of agreements significantly improves efficiency and coordination in the critical stages of the project.